Artificial Intelligence in Teacher Soft-Skill Development: A Review of Educational Initiatives in West Sumatra - Rahadian Zainul; Dony Novaliendry; Budhi Oktavia; Fitrah Mey Harmi Siregar; Maiti Faddila; Hidayatul Husna; Delsya Helvira Suci (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
This study examines the application of artificial intelligence (AI) in developing teachers' soft skills in West Sumatra. AI technology plays an important role in supporting the improvement of communication skills, classroom management, and critical thinking through personalized training and instant feedback. This study uses a qualitative descriptive method with a case study approach to analyze the effectiveness of AI in supporting teacher competency development. The results of the study show that although AI is able to provide positive impacts, the main challenges faced are the digital infrastructure gap and low digital literacy among teachers, especially in remote areas. However, with the support of the right policies and more inclusive training, AI has great potential to improve the quality of education in West Sumatra.